Nonmesonic weak decay spectra of light hypernuclei - Krmpotic, Francisco (2014)
The nonmesonic weak decay spectra of light hypernuclei have been evaluated in a systematic way. As theoretical framework we adopt the independent particle shell model with three different one-meson-exchange transition potentials. Good agreement with data is obtained for proton and neutron kinetic energy spectra of 4ΛHe, and 5ΛHe, when the recoil effect is considered. The coincidence spectra of proton-neutron pairs are also accounted for quite reasonably, but it was not possible to reproduce the data for the neutron–neutron pair spectra. It is suggested that the π + K meson-exchange model with soft monopole form factors could be a good starting point for describing the dynamics responsible for the decays of these two hypernuclei. The 4ΛH spectra are also presented.